Pakistan Strategic Country Environmental Assessment - World Bank (World Bank, Washington, DC, 2020)
The urgency of addressing Pakistan's environmental problems has probably never been greater. Conservative estimates presented in this report suggest that environmental degradation costs the country at least 6 percent of GDP, or about Rs. 365 billion per year, and these costs fall disproportionately upon the poor. The most significant causes of environmental damage identified and estimated in this report are (1) illness and premature mortality caused by air pollution (indoor and outdoor), (almost 50 percent oft he total damage cost); (2) diarrhoeal diseases and typhoid due to inadequate water supply, sanitation and hygiene (about 30 percent of the total), and (3) reduced agricultural productivity due to soil degradation (about 20 percent of the total). The magnitude of these costs indicates that environmental decay has become a serious development concern. Following a discussion of the analytical framework for environmental outcomes, , the report analyzes the main binding constraints to improving environmental performance as falling into four categories, (1) gaps in institutional design, (2) gaps in the regulatory framework, (3) capacity limitations, and (4) gaps in incentives and accountability. Of these, weak incentives and low levels of public accountability remain the critical constraints on performance. Public scrutiny of performance is ultimately a source of strength that leads to stronger institutions with greater public trust and support. The principal features of these constraints are discussed, as are recommendations for moving forward to more sustainable economic growth. The annex (Volume 2) provides a comprehensive overview of the data and methods used to estimate the costs of environmental degradation in three environmental damage categories and three natural resource damage categories: (1) urban air pollution, including particulate matter and lead, (2) water supply, sanitation and hygiene, (3) indoor air pollution, (4) agricultural damage from soil salinity and erosion, (5) rangeland degradation, and (6) deforestation. Data limitations have prevented estimation of degradation costs at the national level for coastal zones, municipal waste disposal, and inadequate industrial and hospital waste management.